Profesionalisme Guru PAUD dalam Menerapkan Kurikulum di Abad 21 - Nur Farida; Pamungkas Stiya Mulyani (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
This study aims to examine in depth the extent of teachers’ efforts and concrete practices in enhancing their professionalism, viewed from personal aspects, the surrounding environment, and policy support from relevant stakeholders, as well as the constraints and challenges faced in implementing the 21st-century curriculum. The research employed a qualitative method with a quasi-qualitative approach, due to limitations of time, cost, and the number of informants, which consisted of 16 (sixteen) early childhood education (ECE/PAUD) teachers from four villages in Mojotengah District, Wonosobo Regency. Data analysis adopted the Miles and Huberman model, with data validation conducted through source and method triangulation. The findings indicate that PAUD teachers demonstrate professionalism in their teaching practices through the use of collaborative, project-based learning methods that incorporate 21st-century technological tools. The application of a facilitator approach by teachers is effective in building communication patterns between teachers and students, thereby fostering students’ 21st-century skills. The enhancement of teacher professionalism is achieved through self-initiative, support from professional organizations, and reinforcement from policy stakeholders.